The miracle of salt : recipes and techniques to preserve, ferment, and transform your food - Duguid, Naomi (Artisan, 2022)
"Through stories, instructions, and over 100 recipes, Duguid illuminates the many foods born from the power of salt-charcuterie, butter, soy sauce, kimchi and sauerkraut, bacalao, and miso-unearthing their importance to their native cuisine and offering home-friendly recipes that highlight the nuances of salt's flavor"--